Navigating the AI-Driven Healthcare Era: A Review of Key Developments - Khan, Murad; Sherani, Abdul Mannan Khan (CV. Multi Kreasi Media, 2024)
The application of Artificial Intelligence (AI) in the provision of healthcare has brought some tremendous changes in medical practices; achieving breakthroughs in diagnostics, treatment and healthcare management. Artificial Intelligence in particular is improving diagnosis identification, disease identification and diagnosis, managing administration information, etc. Chronic disease management: Using artificial intelligence tomorrow’s sicknesses today, using your genes, environment, and even lifestyle/personal choices to deliver more effective cures with minimal side effects. However, several ethical questions are attached to the use of AI in healthcare such as data control, fairness of the algorithms used, and user control and thus for any organization to adopt the use of AI, the following questions should be appropriately answered. Nonetheless, there is a great deal of promise for the application of AI in healthcare including: the alleviation of healthcare inequalities, enhancement on the clinical decision making processes, positive promotion of prevention and patient-centered care delivery. Depending on the further advancement of AI the future in the field of healthcare will include new creations in a predictive analysis of a patient’s condition and in automated systems for a personalized treatment that will improve the operating quality and accessibility of the options for medical services. However, technology and Artificial Intelligence in specifically have the potential of transforming the industry completely than envisaged especially if there shall be set down stringent ethical consideration and research collaboration in this domain by health care professional, technologist, and policymakers. At the end, the purpose of AI in health care is to make health care smarter and superior with the help of human intelligent thus making health care systems efficient, fair towards all patients.